Virulence Phenotypes of Siberian Wheat Stem Rust Population in 2017–2018 - Skolotneva, Ekaterina S.; Kosman, Evsey; Patpour, Mehran; Kelbin, Vasiliy N.; Morgounov, Alex I.; Shamanin, Vladimir P.; Salina, Elena A. (Frontiers in Agronomy, 2020)
Management of wheat stem rust in Western Siberia has gained importance since the first outbreaks in 2007-2010 and 2016. The race composition and virulence patterns were investigated for the enlarged Puccinia graminis f. sp. tritici (Pgt) samples collected in three neighboring regions Omsk, Novosibirsk, and Altai during 2017-2018. Most of Pgt isolates were identified as virulent to wheat lines with genes Sr5, Sr9a, Sr10, Sr38, SrMcN and avirulent to Sr24, Sr31. Differentiation ability of genes Sr6, Sr7b, Sr8a, Sr9b, Sr9d, Sr9g, Sr9e, Sr11, Sr17, Sr21 Sr30, Sr36, and SrTmp to distinguish between the regional populations was established. A total of 33 virulence phenotypes or races were detected among 115 Pgt isolates tested. Based on virulence phenotypes, two different Pgt subpopulations were identified in the Altai and Omsk regions likely originating from asexual and sexual cycles, respectively. The Novosibirsk pathogen population seems to be a mixture of isolates originated from both neighboring regions with virulence phenotypes that developed in the west, Omsk (TKRPF, QHHSF, and MLLTF) and in the south, Altai (NFMSF, LKCSF, LKMSF, and PKCSF) of Western Siberia.